1999
DOI: 10.1002/(sici)1521-3765(19990201)5:2<587::aid-chem587>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Self-Assembling Properties and Incorporation of Carbohydrate-Substituted Porphyrins into Cell Membrane Models

Abstract: A general and very efficient synthesis of new carbohydrate-substituted porphyrins is described. Reaction of porphyrin 6 with different glycosyl imidates 7 a ± g leads to the formation of carbohydrate-substituted porphyrins 9 a ± g in good yield. Subsequent demetallation and removal of the carbohydrate protection groups leads to the metal-free compounds 11 a ± g. In aqueous solution, compounds 11 a ± g tend to form defined water-soluble aggregates in a self-assembling process. In methanol/water mixtures the agg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 12 publications
(13 reference statements)
1
16
0
Order By: Relevance
“…This observation is in line with Grundler and Schmidt's synthesis and attempted glycosylation with donor 6. [34] The donor has due to this only sporadically been used since the work by Schmidt and only to glycosylate reactive alcohols, [35,36] i. e. no carbohydrate alcohols, amino acid alcohols [37] or weak nucleophiles like amides. The inherent problem with glycosylation using a GlcNAc donor could be overcome by using the N-Troc protected donor 7, which gave good yields and high selectivity, when using excess of the donor (entry 19 vs 20).…”
Section: Resultsmentioning
confidence: 99%
“…This observation is in line with Grundler and Schmidt's synthesis and attempted glycosylation with donor 6. [34] The donor has due to this only sporadically been used since the work by Schmidt and only to glycosylate reactive alcohols, [35,36] i. e. no carbohydrate alcohols, amino acid alcohols [37] or weak nucleophiles like amides. The inherent problem with glycosylation using a GlcNAc donor could be overcome by using the N-Troc protected donor 7, which gave good yields and high selectivity, when using excess of the donor (entry 19 vs 20).…”
Section: Resultsmentioning
confidence: 99%
“…1 . It has been shown that aggregation changes the photophysical properties of porphyrin, chlorin, and phthalocyanine photosensitizers [85][86][87][88][89][90][91][92][93][94][95][96]. Aggregation shortens the triplet-state lifetime and decreases the singlet-oxygen quantum yield by dissipating the energy through internal conversion [92][93][94][95][96][97].…”
Section: Amphiphilicitymentioning
confidence: 99%
“…Most of the structures described in the literature are stable in non-polar organic solvents and in the solid phase. Only the classic amphiphils, such as micelles, liposomes, and aggregates of carbohydrate-substituted porphyrines [26], are able to form non-covalent structures in aqueous solutions. Our aim therefore was to design a stable inaqueous solution, non-covalent polymer instead of true polymers ( Figure 2).…”
Section: Self-assembled Molecules Instead Of True Polymersmentioning
confidence: 99%